Optimization Of Compost Maturity From Fruit Waste With The Addition of Rumen Waste and Leachate Bioactivators - Anum Sari, Sri; Izzuddin, M.; Mulyaningsih, Budiyanti (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2025)
Fruit waste generated by vendors in Banjarbaru City has the potential to pollute the environment if not properly managed. One alternative management approach is processing it into compost with the addition of bioactivators. This study aimed to optimize the compost maturation process through the addition of rumen waste and leachate bioactivators. The research was conducted using an experimental design with 12 kg of fruit waste treated with varying doses of rumen waste and leachate bioactivators. The observed parameters included temperature, pH, moisture content, and compost quality based on organic carbon, nitrogen, phosphorus, and potassium content, in accordance with the Indonesian National Standard (SNI 19-7030-2004). The results showed that the combination of 0.5 kg of rumen waste and 1.5 liters of leachate (D2) provided optimal temperature, pH, and moisture conditions to accelerate compost maturation and produced compost with characteristics that met the standard. In conclusion, this combination was effective in accelerating decomposition and improving compost quality, although further studies are needed regarding nutrient content analysis and the development of a more efficient composter design.